Eclipse - Meyer, Stephenie (New York : Little, Brown, 2007)
Bella must choose between her friendship with Jacob and her relationship with Edward, both vampires, but when Seattle is ravaged by a mysterious string of killings, the three of them need to decide whether their personal lives are more important than the well-being of an entire city.
"Megan Tingley books."
KLIATT
Keywords: Vampires -- Fiction